Impact of weather variables on yield and yield attributes in Okra under different growing environments - S. K. DHANKHAR; D. P. DESWAL; SURENDER SINGH (Journal of Agrometeorology, 2012)
Okra variety Hisar Unnat was sown on eight different dates during March to July of 2008 and 2009. Results revealed that high seed yield was obtained in okra sown on 15th June, 25th June and 5th July Seeds per fruit, test weight and standard germination were also found superior during this period. Average relative humidity had significantly positive correlation with seed yield (r=0.76), number of seeds per fruit (r=0.72), test weight (r=0.79) and standard germination (r=0.79). Maximum, minimum and mean temperatures and evaporation expressed significantly negative association with above parameters. High seed yield of okra can be harvested, when maximum, minimum, and mean temperature remains around 33.5-36oC, 19.5-24oC, and 26.9-30oC, respectively with average relative humidity 65-75% and 4.1 -5.7 mm evaporation. Seed yield prediction would be more reliable when temperature, relative humidity and evaporation were taken together instead of individual weather variable in regression equation.